(3fXGe GdESJNHGQGJ GdJShjbjIs - (3YdGA aQMGf(B, (3WGdHs; (3eMeO LHGQ GdTeQj(B, s ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2009)
(3jVe GdefgLjI hGdOQGSGJ GdSGHbI, GdEWGQ GdfXQj, GdEWGQ GdYedj, GdESJfJGLGJ hGdJhUjGJs
(3GdedGMb U(B.199 (3GdeQGLY U(B.211s
Keywords: (3COGQI GdeHjYGJs; (3GdESJQGJjLjI GdJfGaSjIs; (3GdJShjbs